Implementation of the Wadiah Contract in the Practice of the Eid Savings Scheme from the Fathul Qorib Perspective - Afida Mariani Kamila; Lely Ana Ferawati Ekaningsih (ICO EDUSHA, 2025)
This study aims to analyze the implementation and sharia compliance of the wadiah yad dhamanah contract in the tabungan hari raya (holiday savings) product at uspps blokagung-banyuwangi through a qualitative case study. Using the Kitab Fathul Qorib as the primary normative perspective, data was collected through interviews, observation, and document studies, and then analyzed using the Miles and Huberman interactive model. The findings indicate uncertainty, despite the formal fulfillment of the contract's pillars through the application of wadiah yad al-dhamanah. An in-depth analysis reveals three substantive deviations. First, the customers' low understanding of the nature of the trust (deposit) contract creates gharar (uncertainty) and erodes the principle of ridha (mutual consent) emphasized in Fathul Qorib. Second, the practice of a fixed, promoted "Certainty Bonus" of 5% has transformed the voluntary nature of a hibah (gift) into an expected return, approaching the realm of syubhat riba al-nasi'ah (suspicion of usury related to delay). Third, an inconsistency was found between the legal construct of the wadiah contract and the logic of benefit distribution equated with profit-sharing, creating legal ambiguity (talfiq al-‘uqud). This study concludes that sharia compliance cannot be adequately assessed solely from formal adherence but requires substantive integrity encompassing clarity, transparency, and coherence with classical fiqh principles. Recommendations focus on transparent contract reformulation, comprehensive customer education, and strengthening sharia supervision based on the authority of classical Islamic texts. Keywords: Wadiah yad dhamanah contract, Fathul Qorib, Sharia Compliance.